The comparative characteristic of monolayer and three-dimensional cultivations of the continuous cell line of fibroblasts L 929 - Moisieiev, A.I.; Bozhok, G.A.; Gorina, O.L. (Reports of the National Academy of Sciences of Ukraine, 2019)
The comparative study of the functional and metabolic potentials of fibroblasts of cell line L 929 under conditions of the monolayer (2D) and threedimensional cultivations is performed. It is found that the method of cultivation of fibroblasts affects their viability and proliferative potential. In particular, it is shown that, after the volumetric cultivation of fibroblasts during 7 days, the number of viable cells and their proliferative potential significantly (p < 0.05) exceed similar indicators after the monolayer cultivation. According to data of the gel permeation chromatography, we established significant differences (p < 0.05) in the quantitative and qualitative compositions of proteinpeptide substances in cell culture media in 2D and 3D formats. Special attention is attracted by the results on the difference in the amounts of peptides in the range of molecular masses (705—1607 Da) in the medium of volumetric cultivation, which may be due to the active synthesis of growth factors. The results obtained indicate that the volumetric cultivation has a significant impact on the synthetic and morphofunctional indicators of fibroblasts of the cell line L 929 in comparison with the 2D format.